Further Contribution to the Grass Flora of Gujarat - Desai, Rinku J.; Raole, Vinay M. (Indian Forester, 2012)
Regular field survey for 2 years revealed the presence of seven new grases which were not reported earlier and collected for the first time from Gujarat state. Their detailed morphological and reproductive features were studied.